Impact of prenatal exercise on neonatal and childhood outcomes: a systematic review and meta-analysis. Issue 21 (18th October 2018) - Davenport, Margie H; Meah, Victoria L; Ruchat, Stephanie-May; Davies, Gregory A; Skow, Rachel J; Barrowman, Nick; Adamo, Kristi B; Poitras, Veronica J; Gray, Casey E; Jaramillo Garcia, Alejandra; Sobierajski, Frances; Riske, Laurel; et al.
Abstract : Objective: We aimed to identify the relationship between maternal prenatal exercise and birth complications, and neonatal and childhood morphometric, metabolic and developmental outcomes. Design: Systematic review with random-effects meta-analysis and meta-regression. Data sources: Online databases were searched up to 6 January 2017. Study eligibility criteria: Studies of all designs were eligible (except case studies and reviews) if published in English, Spanish or French, and contained information on the relevant population (pregnant women without contraindication to exercise), intervention (subjective/objective measures of frequency, intensity, duration, volume or type of exercise, alone ('exercise-only') or in combination with other intervention components (eg, dietary; 'exercise+cointervention')), comparator (no exercise or different frequency, intensity, duration, volume, type or trimester of exercise) and outcomes (preterm birth, gestational age at delivery, birth weight, low birth weight (<2500 g), high birth weight (>4000 g), small for gestational age, large for gestational age, intrauterine growth restriction, neonatal hypoglycaemia, metabolic acidosis (cord blood pH, base excess), hyperbilirubinaemia, Apgar scores, neonatal intensive care unit admittance, shoulder dystocia, brachial plexus injury, neonatal body composition (per cent body fat, body weight, body mass index (BMI), ponderal index), childhood obesity (per cent body fat, body weight, BMI) and developmental milestones (including cognitive, psychosocial, motor skills)). Results: A total of 135 studies (n=166 094) were included. There was 'high' quality evidence from exercise-only randomised controlled trials (RCTs) showing a 39% reduction in the odds of having a baby >4000 g (macrosomia: 15 RCTs, n=3670; OR 0.61, 95% CI 0.41 to 0.92) in women who exercised compared with women who did not exercise, without affecting the odds of growth-restricted, preterm or low birth weight babies. Prenatal exercise was not associated with the other neonatal or infant outcomes that were examined. Conclusions: Prenatal exercise is safe and beneficial for the fetus. Maternal exercise was associated with reduced odds of macrosomia (abnormally large babies) and was not associated with neonatal complications or adverse childhood outcomes.